Digital Ecosystem Models in Teacher Professional Development: A Narrative Review of CPD Frameworks (2015–2024) - Finda Vericha Ngenda; Aslamiah Aslamiah; Noorhapizah Noorhapizah; Novitawati Novitawati; Arief Aulia Rahman (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study analyzes digital ecosystem models in teacher professional development (CPD) through a narrative literature review of 30 international journal articles published between 2015 and 2024. Using purposive selection and thematic synthesis, the study identifies four interconnected models: digital collaborative professional learning, data-driven and personalized CPD, hybrid and blended CPD ecosystems, and AI-enhanced microlearning CPD. Rather than treating these models as separate approaches, this study reconceptualizes digital CPD as an integrated ecosystem in which collaboration, personalization, hybridity, and AI support operate as interdependent components. The findings show that digital ecosystems expand opportunities for teacher collaboration, adaptive feedback, flexible learning, and personalized support across diverse educational contexts. However, effectiveness depends not only on technological adoption, but also on the alignment between teachers’ digital literacy, infrastructure readiness, program design quality, and school leadership. By moving beyond descriptive categorization, this study offers an integrative and explanatory framework for understanding sustainable teacher learning across contemporary educational settings and the digital era.